High Altitude 2013
DOI: 10.1007/978-1-4614-8772-2_2
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Defenses Against Hypoxia

Abstract: The ability to cope with hypoxia is essential for the development and survival of all vertebrate species. Cellular hypoxia occurs when oxygen demand exceeds oxygen supply. The development of cellular hypoxia depends both on the type of tissue and partial pressure oxygen (PO 2 ) in the tissue, because cells can vary extremely in their physiologic oxygen demand. Under normal conditions up to 90 % of the available oxygen is consumed by mitochondria to yield ATP through oxidative phosphorylation. Thus, oxygen depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 102 publications
0
13
0
Order By: Relevance
“…Among the candidate genes for the plateau adaptations, five ( IFNGR2 , MAPK4 , NOX4 , SLC2A4 , and PDK1 ) were located in the classical HIF-1 (hypoxia-induced factors) pathway, which plays a central role in regulating cellular responses to hypoxia ( Frede and Fandrey 2013 ); four were found in the corresponding downstream vascular endothelial growth factor (VEGF; RRAS and MAPK4 ) and glycolysis/gluconeogenesis ( KIF2A and KHSRP ) pathways; and five ( ARHGEF19 , STK17A , MAPK4 , PPP1R1A and PRKG1 ) were found in the vascular smooth muscle contraction (VSMC) pathway, which adjusts the diameter of blood vessels and the delivery of blood oxygen ( fig. 7 A ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the candidate genes for the plateau adaptations, five ( IFNGR2 , MAPK4 , NOX4 , SLC2A4 , and PDK1 ) were located in the classical HIF-1 (hypoxia-induced factors) pathway, which plays a central role in regulating cellular responses to hypoxia ( Frede and Fandrey 2013 ); four were found in the corresponding downstream vascular endothelial growth factor (VEGF; RRAS and MAPK4 ) and glycolysis/gluconeogenesis ( KIF2A and KHSRP ) pathways; and five ( ARHGEF19 , STK17A , MAPK4 , PPP1R1A and PRKG1 ) were found in the vascular smooth muscle contraction (VSMC) pathway, which adjusts the diameter of blood vessels and the delivery of blood oxygen ( fig. 7 A ).…”
Section: Resultsmentioning
confidence: 99%
“…Strong selective signals ( F ST ≥ 0.2722) were highlighted in eight genes ( EPO, TLR4, PIK3CA, PRKCA, EGLN3, EGLN2, IFNGR2 , and CUL2 ; fig. 6 A ) known to be important components of the HIF-1 (hypoxia-induced factors) pathway (Frede and Fandrey 2013), indicating potential roles for these genes in high-altitude hypoxia adaptation in Tibetan sheep. Specifically, one prominent candidate gene EPO encodes a secreted glycosylated cytokine and binds to the erythropoietin receptor to control erythrocyte production.…”
Section: Resultsmentioning
confidence: 99%
“…7 A ), which have been reported to affect high-altitude environment adaptation in humans and animals (Storz et al. 2009, 2010; Frede and Fandrey 2013; Natarajan et al. 2013; Projecto-Garcia et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a detailed description of the relevant functions and pathway to candidate genes see Table 1. Among them, three (PIK3R1, IGF1R and PDK1) were located in the classical HIF-1 pathway, which played a central role in regulating cellular responses to hypoxia [21][22][23]; ve were found in the corresponding downstream vascular endothelial growth factor (VEGF, FZD4 and IFNB2) and glycolysis/gluconeogenesis pathways (ATF3, PPCK1 and PFKFB2). The dysregulation of genes in these relevant pathways indicated that hypoxia-induced factors, angiogenesis, and glycolysis metabolism are the most important factors that allowed sheep to manage extreme hypoxic environmental pressure.…”
Section: Lncrna-mrna Co-expression Network Constructionmentioning
confidence: 99%